Economic values of Tanjung Piai National Park wetland conservation in Johor, Malaysia - Wan Yusof, Wan Sofiza Eliana (2018)
Tanjung Piai National Park (TPNP) is a part of the Important Bird Area (IBA) and known as a Ramsar and Wetland of International Importance site. This study investigates visitor’s willingness to pay (WTP) towards conservation and management in the area and estimates the visitors’ preferences towards wetland biodiversity attributes in the TPNP. Data are obtained through questionnaires distribution among 500 randomly chosen visitors between June to October 2014. Factor analysis (FA), contingent valuation method (CVM) and choice experiment (CE) methods were employed in the study, in which visitors are found to visit the area for visit, attraction and relieve purposes. Meanwhile, price of bid, income and gender are the most important and significant factors that influence and determine the level of WTP for the conservation fee among the visitors. Respondents’ current income and expenses are the main considerations in determining the maximum entrance fee, with RM 11.72 was chosen as the most preferred amount. In the choice experiment (CE), visitors’ preference for wetland management and conservation attributes are estimated based on their attributes. Attributes for management aspect were protection level (PL), availability of park guide (PG), amenities (AMM), provide information (INFO), and entrance fee (FEE), while attributes for conservation aspect were extension of park area (EPA), aesthetic appearance (AA), wildlife species and observation habitat quality (WO), habitat quality (HQ) and conservation fee (FEE). Most visitors preferred the medium amenities (AMM), fair wildlife species and observation (WO), and fair habitat quality (HQ). Findings and recommendation from this study are believed to provide useful information to policymakers, government, Johor National Park Corporation (JNPC), and the public to better comprehend the present policies regarding the wetland biodiversity in TPNP. Besides, the valuation results can help to convince the government and any involved decision maker to allocate more resources and funding for conservation activities.